The Usefulness of Perfusion Magnetic Resonance Imaging with Arterial Spin Labeling in the Perioperative Management of Carotid Artery Stenting - Mizuhashi, Satomi; Kohyama, Shinya; Sato, Motoki; Fukuda, Kazumasa (Journal of Neuroendovascular Therapy, 2018)
Objective: For perioperative management after carotid artery stenting (CAS), it is important to predict hyperperfusion syndrome (HPS). In this study, we qualitatively evaluated cerebral blood flow during the perioperative period following CAS using the pulsed arterial spin labeling (ASL) method, and examined the usefulness of this method. Furthermore, we devised the labeling position so that there was no influence of stenting, reducing errors before and after CAS.Methods: Of patients with carotid artery stenosis who underwent CAS in our hospital between June 2015 and December 2016, the subjects were 13 in whom ASL could be performed before and after CAS. ASL was performed within 1 week before CAS, as well as 1 and 7 days after CAS. For blood flow assessment, differences in the cerebral cortex at the basal ganglia level between the left and right and between the preoperative and postoperative states after CAS were qualitatively compared.Results: After CAS, favorable dilation at the lesion site was achieved in all patients. Before CAS, ASL on the affected side showed a reduction in blood flow in nine patients although qualitative assessment was conducted. The day after procedure, findings presage of HP were obtained on ASL in four patients. Of these, HP syndrome-related internal capsule hemorrhage was noted in one case. ASL 7 days after CAS facilitated the assessment of an improvement in cerebral blood flow in comparison with the preoperative state in nine patients.Conclusion: In perioperative management following CAS, ASL is a rapid, noninvasive procedure, facilitating repeated imaging in a short period. This procedure was useful for evaluating cerebral blood flow.